Cyber Security: towards a safe and secure cyber environment - Awang Lah, Mohamed; Raja Othman, Raja Azrina; Abdul Aziz, Normaziah; Mansor, Dzaharudin (Academy of Sciences Malaysia (ASM), 2018)
This document aims to propose strategies in dealing with cyber security issues that affect the national infrastructure, business environment and well being of citizens. The Internet has changed the way people live by enabling economic growth and providing alternative platforms for people to communicate and cooperate. We are starting to see the impact of new 4th Platform technologies (refer to Annex B) such as Internet of Things (IoT) and Artificial Intelligence (AI) poised to fuel digital disruption at an accelerated pace globally. This will further expand cyberspace as well as the value of using it. Our vision for Malaysia is to create a safe and secure cyber environment for the well-being of citizens and wealth creation, in addition to establishing resilient and secure critical national information infrastructure, which is guided by core values of integrity, equitable and prosperous society for social and business activities.